O pewnej metodzie interpolacji współczynnika płodności i o pewnym parametrze natężenia urodzeń - Simeonoff, Emanuel (Wydział Prawa i Administracji UAM, 1967)
The paper deals with two subjects: 1) a method of interpolation resting on a variability principal, 2) the weighed kinetic energy in a birth process. The said method of interpolation leads to an assessment of the values of a function, which in that context represent the coefficient of fertility functionaly depending on a women's age. It has been represented with the help of birth coefficients for women in the fertility group of age (15—60 years) living in Bulgaria in the years 1947—1956. The deliberations with regard to the second problem lead to the construction of parameter T, showing the birth intensity. That parameter rests on fertility and parameter k, calculated on the basis of fertility and death rates. The relations existing between those two parameters and their dependency on fertility are being illustrated by empirical data.
On a method of interpolation of fertility rates and on a new parameter of birth intensity